صكوك المضاربة والمشاركة في ضوء البيان الصادر عن هيئة المحاسبة والمراجعة للمؤسسات المالية الإسلامية لعام 2008 : التحديات والفرض Sukuk al-Mudharibah w al-Musharikah fi Dhu'i al-Bayani al-Shadiri an Hyna al-Makhasibah wa al-Maraji'ah lil Mu'sasati al-Maliah al-Islamiyah lil Am 2008: al-Takhdidiyyah wa al-Farsd - Engku Ali, Engku Rabiah Adawiah (Jabatan Kemajuan, 2009)
This article attempts to highlight some recent developments and issues in the sukuk market, especially in the light of the AAOIFI Shari`ah pronouncement of February 2008. In general, the market tends to understand and expect sukuk to be within the “fixed income” types of investment with minimal or controlled risks and capital preservation features. In short, they expect sukuk to behave like conventional bonds in terms of capital preservation, periodic distribution frequency and rate of return. When sukuk use debt-based structures and lease-based structures, it is not that difficult to meet this fixed income characterisation. However, when sukuk start to use equity contracts like mudarabah and musharakah, such fixed income characteristic created some anomalous situations and conflicts. There are apparently inherent contradictions in the nature of mudarabah and musharakah as equity contracts, and capital preservation and fixed income nature of debt market environment in which sukuk are expected to operate. Thus, additional “credit enhancements” and strategies were introduced to the mudarabah and musharakah sukuk structures to achieve capital protection and predictable periodic returns similar with other fixed income or bonds instruments. These credit enhancements to equity-based sukuk had been the subject of strong criticisms by various parties in terms of their compliance with the Shari`ah requirements of mudarabah and musharakah contracts. This had led to the practices being reviewed by the Shari`ah Board of AAOIFI. They finally came up with the February 2008 AAOIFI pronouncement that highlighted in unequivocal terms that sukuk are inherently different from conventional bonds and fixed income instruments, and thus, should behave differently. It was also understood from the pronouncement that when the sukuk structure is equity-based, certain basic rules of equity cannot be compromised for the sake of meeting the commercial demand of the market, which actually is conditioned by the prevalent interest-based economy and philosophy. The AAOIFI pronouncement gave rise to a re-examination of market perception of sukuk. Sukuk should not and could no longer be perceived as strictly fixed income instruments with capital preservation features. If the pronouncement is stringently adhered to, the equity-based sukuk should behave like equity instruments and not to be tweaked to fit into the “fixed income box